The Liouville theorem for the Cordes type elliptical system of high order - Kalita , E. A. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
We study a quasilinear elliptic system in a Euclidean space with a Douglis—Nirenberg structure. We introduce a cordesicity condition for a system which guarantees that Liouville theorem holds: if the rate of growth of the generalized solution of a system at infinity is less than the limit rate which depends on cordesicity indices, then this solution is a polynomial of a specific degree.